ANALISIS PENERAPAN SISTEM MANAJEMEN KESELAMATAN KONSTRUKSI PADA PROYEK JALAN BY PASS MAMMINASATA - Basyar Bustan; Andi Erdiansa (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The frequency of construction accidents occur in several road construction projects is very high. PUPR prepares SMKK Guidelines for implementation. However, many service providers have not implemented it optimally. The aim of the research is to obtain the level of SMKK implementation. obtain the dominant factors that are obstacles in implementing SMKK, obtain recommendations for improving the performance of implementing SMKK in the Mamminasata By Pass Project. The variables used in this research are elements in the SMKK Guidelines. This research uses Analytical Hierarchy Process method with the Expert choice application. The implementation of SMKK in the Mamminasata Road Project is classified in the satisfactory category with a percentage level of 86.4%. Factors that become obstacles to the implementation of the Construction Safety Management System are the absence of receipt, storage, use and destruction of materials and B3; then some workers from this project do not have expertise certificates appropriate to their field; This project also does not have operational controls on supply chain control. The strategy to increase implementation is that service providers and service users must strictly select prospective employees with competent workforce requirements and procedures; cooperate with subcons; and it is recommended to use the supply chain.